Campaign Billboards as Veritable Sources of Information for the Nigerian Electorate: A Case Study of Benin City - Ossai-Ugbah, Ngozi Blessing (Communicate: Journal of Library and Information Science, 2023)
This study examined campaign posters and billboards as veritable sources of information for Nigerian electorates in the 2023 Presidential, national, and state assembly elections. The research was limited to Benin and delimited to Ugbowo, headquarters of Egho local government area of Edo State, Nigeria. The objective was to establish if people read campaign posters and billboards and if the respondents considered them as sources of information. This study employed a descriptive survey method. A total of one hundred questionnaires (100) were distributed and eighty-nine (890) were retrieved. The findings revealed that 80 respondents (89.89%) considered campaign posters and billboards as sources of information for electorates. Campaign posters and billboards were read for information, especially for the manifesto. The study recommended amongst others that information managers and librarians should consider the use of posters and billboards in sensitization campaigns.